Underlying Institutional Factors Affecting Student’s Absenteeism in Higher Education Institutions - Ihtisham-Ul-Haq; Muhammad Nisar; Fazal Hanan; Khurram Shahzad (Journal of Religion and Society, 2025)
Student’s’ absenteeism remains a major issue in higher education that has serious implications for student engagements, academic achievement, and institutional effectiveness. While in Pakistan, contemporary researchers highlighted socioeconomic factors, limited empirical attention has been given to institutional factors of absenteeism at university level; this study will help to address this gap by investigating the association between the institutional factors and student absenteeism in public sector educational institutions in Khyber Pakhtunkhwa Pakistan. The main objective of the study was to examine the relationship between student’s absenteeism and the institutional factors like teaching methods, classroom environment, academic organization, assessment process, accessibility of learning materials and the practicality of implications. Study adopted the quantitative research design. A survey was conducted with 374 respondents of Bacha Khan University in Charsadda using a well-structured Likert-scale. To establish the relationship between student’s absenteeism and institutional factor, chi-square test was employed. The results showed that there was a statistically significant relationship between student absenteeism and various institutional factors like lack of clarity in the explanation of lesions, ineffective teaching method, ineffective classroom discipline, dull and overly theoretical learning, schedule clashes, large class sizes, and slow feedback on homework, insufficient laboratory facilities, and lack of extracurricular academic support. The study recommended that universities should adopt interactive and student’s centered approaches in teaching methodologies, smooth academic schedule, improve academic support services, increase learning facilities, and create good learning environments to promote attendance and academic success. Keywords: Student Absenteeism, Institutional Factors, Teaching Methodologies, Academic Environment, Student’s